Sustainable institutional investors and corporate biodiversity disclosure: Does sustainable board governance matter? - Patrick Velte (Corporate Social Responsibility and Environmental Management, 2023)
The purpose of this study is to examine the impact of sustainable institutional investors (SIIs), based on their signatory status to the UN Principles for Responsible Investment (PRI), on corporate biodiversity disclosure (BD). Moreover, the moderating influence of sustainable board governance (critical mass of female directors, sustainability committees, and sustainability-related executive compensation) as a possible channel of the link between SIIs and BD is analyzed. The study is based on a European sample consisting of 2319 firm-year observations between 2014 and 2020 (EUROSTOXX 600) and embedded in a stakeholder agency theoretical framework. The results are in line with prior research on sustainable corporate governance and indicate that SIIs have a positive impact on BD and that the included sustainability board governance index strengthens this link. Our results are robust to a battery of sensitivity analyses. This study makes a major contribution to prior analyses, as it appears to be the first study on the link between SIIs and BD and the moderating impact of sustainable board governance. The study has major implications for business practice, regulators and research.
Keywords: 650; biodiversity disclosure; institutional investor; sustainable corporate governance; sustainable investor